Trauma, fantasy and subjectivity formation through a Lacanian approach in Khaled Hosseini’s novels - Haghighi, Hanieh (2017)
The history of Afghanistan teems with several coup d’états, civil wars, foreign military interventions, and rigorous tribalism along with ethical and sexual discriminations which all have left several traumatized generations in this country. So far, a number of scattered Afghan poets expressed their bitter experience of war, and its traumatic outcomes in their Persian and Pashtun poems; however, the first Afghan writer, who expressed these factors and attracted the world’s attention to the sufferings and troubles of his nation, was the Afghan-American physician, Khaled Hosseini. Hosseini is a master of narrating a certain kind of story in which unbearable traumatic events including violence, abuse, and misery are made readable. The main pillars of his novels are the illustration of traumatic events including war, loss, rape, domestic abuse and violence which shape, design, and propel the story having serious influence on the subjectivity of his characters. As result, his works are proper to be worked on regarding the social, psychoanalytical-philosophical concept of trauma and its impacts on subjectivity formation in order to open a new perspective in the horizon of literary-cultural studies relying on the ideas of the French psychoanalyst, Jacques Lacan. Lacan regards trauma as something that creates the subject forever. He also holds the viewpoint that all subjects are essentially traumatized through the separation from the mother and the entrance into the realm of language. However, their encounter with the Real reoccurs over and over throughout their lives creating their subjectivities in trauma. As an outcome of trauma, fantasy functions as a space for the manifestation of unconscious desires and is a way in which subjects structure or organize their desires as a defense against the helplessness of not being. Only the subjects who can traverse their fantasies are able to recover from trauma and create a new subjectivity. Adopting a Lacanian approach, this research addresses the impact of trauma as the main source of people’s actions and a basic factor in their self-perception, on the subjectivity formation of the characters of Hosseini’s novels, namely The Kite Runner, A Thousand Splendid Suns, and And the Mountains Echoed, and reveals the function of fantasies, as the designers of the framework through which a subject perceives reality, in their lives. It also examines whether any of the characters traverse the fantasy to build a new subjectivity. In order to achieve the aforementioned objectives, this research identifies the external stimuli causing trauma in the characters’ lives to examine how these psychological scars affect the formation of their subjectivities, and employs a close reading of the texts focusing on the narrative, the dialogues and monologues of the characters, the description of their dreams, and also their behaviors which all reflect the characters’ desires, fantasies, and consequent traversing from them. Finally, the present study reveals how some characters including Amir, Laila and Pari and Pari Wahdati recover from trauma through traversing their fantasies and build new subjectivities, and some including Mariam, Abdullah and Nila fail in creating new subjectivities by recovering from Trauma due to their inability to traverse their fantasies.